2016
DOI: 10.13189/ujer.2016.040608
|View full text |Cite
|
Sign up to set email alerts
|

Learning, Tablet, Culture—Coherence?

Abstract: This paper presents understandings of learning in schools where Internet-enabled Information and Communication Technologies (ICTs) are taken for granted. The context is a full-scale 1:1 tablet project in Danish municipality schools where this study bring forward expressions of learning from one class (12-13 year old children) in order to offer interpretations of how the learning is possible to relate to the use of the tablet and the municipality intentions of changing the teaching and learning culture. The aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…Some no-model-based studies also assessed general perceptions, sometimes identified as attitudes, without relying on a clear theoretical definition. Overall, the studies show that attitudes and general perceptions are positive (Duran and Aytaç 2016;Ferguson 2017;Huang et al 2017;Hyppa-Martin et al 2016;Pruet et al 2015;Tay 2016) and tablets seem to be wellintegrated into learning culture (Norqvist 2016).…”
Section: Attitude and General Perceptionsmentioning
confidence: 87%
See 2 more Smart Citations
“…Some no-model-based studies also assessed general perceptions, sometimes identified as attitudes, without relying on a clear theoretical definition. Overall, the studies show that attitudes and general perceptions are positive (Duran and Aytaç 2016;Ferguson 2017;Huang et al 2017;Hyppa-Martin et al 2016;Pruet et al 2015;Tay 2016) and tablets seem to be wellintegrated into learning culture (Norqvist 2016).…”
Section: Attitude and General Perceptionsmentioning
confidence: 87%
“…Surveys were based on previous empirical studies, from previous interviews, or by the authors according to the assessed concepts, but not from validated questionnaires linked to specific theoretical models. We noted that Norqvist (2016) and Kontkanen et al (2017) can be distinguished by their use of specific data collection methodologies. Norqvist (2016) used an original interview method based on the theory of group cognition.…”
Section: Methodologies In No-model-based Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The digitalisation of K-12 education has developed rapidly worldwide through so-called one-to-one computing initiatives based on one laptop or tablet for each student (Islam & Grönlund, 2016). In the Nordic countries, studies of teacher practices in one-to-one computing classrooms have been made in Sweden (Fleischer, 2013;Håkansson Lindqvist, 2015;Tallvid, 2015), in Norway (Blikstad-Balas, 2012;Elstad & Christophersen, 2017), and in Denmark (Lorentzen, 2012;Norqvist, 2016), while Finland still seems to be a blind spot on this map (Bocconi, Kampylis, & Punie, 2013). Important knowledge and understanding about Finnish teacher practices in the one-to-one computing classroom is, therefore, not available.…”
Section: Introductionmentioning
confidence: 99%
“…The Swedish school context demonstrates rich digitalisation by one-to-one computing initiatives. Several studies, internationally and nationally, have focused on the role of one-to-one computing in schools, including studies about the innovative use of one-to-one computing and its potential for changing and modernising teaching and learning (Bocconi, Kampylis, & Punie, 2013), teachers' teaching (Pegrum, Oakley, & Faulkner, 2013;Håkansson Lindqvist, 2015;Player-Koro & Tallvid, 2015;Saudelli & Ciampa, 2014;Bergström, Mårell-Olsson, Häll, & Kumar, 2017), and pupils' use (Håkansson Lindqvist, 2013;Tallvid, Lundin, Svensson & Lindström, 2015;Norqvist, 2016). Few studies have focused on principals' strategic leadership and organisation of schools' processes of digital transformation through one-to-one computing initiatives.…”
Section: Introductionmentioning
confidence: 99%